43.8k views
4 votes
Using the polynomials Q = 3x 2 + 5x - 2, R = 2 - x 2, and S = 2x + 5, perform the indicated operation.

Q - [R + S]
2x2 + 3x - 9
4x2 - 3x + 9
2x2 - 3x + 9
4x2 + 3x - 9

User DGrady
by
5.4k points

1 Answer

4 votes

Answer:

(D) 4x² +3x -9

Explanation:

Q -[R+S] =(3x²+5x - 2) -[(2 - x²)+(2x+5)] = (3x²+5x - 2) -[2 - x²+2x+5] =

(3x²+5x - 2) -[ - x²+2x+7] = 3x²+5x - 2+x² - 2x - 7 = 4x² +3x -9

User Svelandiag
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.